Testing the efficacy of antimicrobial peptides in the topical treatment of induced osteomyelitis in rats - Melicherčík, Pavel; Čeřovský, Václav; Nešuta, Ondřej; Jahoda, David; Landor, Ivan; Ballay, Rastislav; Fulín, Petr (Folia microbiologica, 2018)
Joint replacement infections and osteomyelitis are among the most serious complications in orthopaedics and traumatology. The risk factors for these infections are often bacterial resistance to antimicrobials. One of the few solutions available to control bacterial resistance involves antimicrobials, which have a different mechanism of action from traditional antibiotics. Antimicrobial peptides (AMP) appear to be highly promising candidates in the treatment of resistant infections. We have identified several AMP in the venom of various wild bees and designed analogues that show potent antimicrobial activity and low toxicity against eukaryotic cells. The aim of the present study was to test the efficacy of one of those synthetic peptide analogues for the treatment of acute osteomyelitis invoked in laboratory rats. Femoral cavities of 20 laboratory Wistar rats were infected with Staphylococcus aureus. After 1 week, eight rats received an injectable calcium phosphate carrier alone, another eight rats were treated with a calcium phosphate mixed with AMP, and four rats were left without any further treatment. After another week, all rats were euthanized and radiographs were made of both the operated and healthy limbs. The animals with the carrier alone exhibited more severe acute osteomyelitis on radiographs in comparison to the recipients of the calcium phosphate carrier loaded AMP and untreated infected individuals. Based on the results of the above mentioned experiment, it was concluded that when injected directly into the site of femoral acute osteomyelitis, the calcium phosphate carrier mixed with AMP reduced osteomyelitis signs visible on radiographs.
Keywords: Rats; Anti-Bacterial Agents; Staphylococcal Infections; Rats, Wistar; mužské pohlaví; osteomyelitida; stafylokokové infekce; Staphylococcus aureus; krysa rodu Rattus; Peptides; fosforečnany vápenaté; zvířata; Humans; Osteomyelitis; antibakteriální látky; peptidy; potkani Wistar; Calcium Phosphates; lidé; Male; Animals